Influence of Phonological Awareness, Morphological Awareness and Non-verbal ability on Reading Comprehension in Malayalam - Abdul Gafoor, K & Remia, K. R (Guru Journal of Behavioral and Social Sciences, 2013)
In the context of observations that students lack mastery of elementary reading comprehension in Malayalam even by the end of 5-7 years of formal schooling, this study applies multiple regression analysis for reading comprehension. Longitudinal survey data from a representative sample of 159 lower primary students from grade 2 to 4 revealed Reading Comprehension as significantly and positively related to Morphological Awareness, Phonological awareness and Ravens non-verbal ability. The three predictors account for near 1/3 of the variation in reading comprehension in Malayalam of elementary school learners. Findings suggest enhancing phonological and morphological awareness in order to develop reading comprehension.